Critical Pedagogy as Counter-Hegemony: Reorienting Islamic Religious Education Against Digital Radicalism and Disinformation - Moh.Abdullah; Rufai Bello; Nurfajriyani (MD Research Center, 2026)
The proliferation of digital disinformation and radical ideologies in cyberspace has triggered a crisis of critical thinking among Muslim youth, challenging the integrity of Islamic Religious Education (PAI) as a space for liberation and ethical formation.This study employs a critical literature review design, synthesizing theories from critical pedagogy (Freire, Giroux), digital media studies, and Islamic education scholarship to construct a transformative pedagogical framework. The research aims to analyze the mechanisms of digital hegemony in shaping religious consciousness and to propose the integration of critical pedagogy into PAI as a counter-hegemonic strategy. The analysis reveals that critical pedagogy enables a fundamental paradigm shift in PAI, from an indoctrinative model to an emancipatory one, fostering critical consciousness (conscientization), dialogical learning, and socio-ethical resilience against radical narratives. It is argued that a critically-oriented PAI is essential for cultivating a generation that is not only religiously observant but also critically aware, inclusive, and capable of navigating the complexities of the digital age. This requires curricular reorientation, teacher training as facilitators of critical awareness, and the development of contextualized teaching materials.